Archaeal Communities in Deep Terrestrial Subsurface Underneath the Deccan Traps, India - Dutta, Avishek; Sar, Pinaki; Sarkar, Jayeeta; Dutta Gupta, Srimanti; Gupta, Abhishek; Bose, Himadri; Mukherjee, Abhijit; Roy, Sukanta (Frontiers in Microbiology, 2019)
Archaeal community structure and potential functions within the deep, aphotic, oligotrophic, hot, igneous province of ~65 Myr old basalt and its Archean granitic basement was explored through archaeal 16S rRNA gene amplicon sequencing from extracted environmental DNA of rocks. Rock core samples from three distinct horizons, basaltic (BS), transition (weathered granites) (TZ) and granitic (GR) showed limited organic carbon (4–48 mg/kg) and varied concentrations (<1.0–5000 mg/kg) of sulfate, nitrate, nitrite, iron and metal oxides. Quantitative PCR estimated the presence of nearly 103-104 archaeal cells per gram of rock. Archaeal communities within BS and GR horizons were distinct. The absence of any common OTU across the samples indicated restricted dispersal of archaeal cells. Younger, relatively organic carbon- and Fe2O3-rich BS rocks harbor Euryarchaeota, along with varied proportions of Thaumarchaeota and Crenarchaeota. Extreme acid loving, thermotolerant sulfur respiring Thermoplasmataceae, heterotrophic, ferrous-/H-sulfide oxidizing Ferroplasmaceae and Halobacteriaceae were more abundant and closely interrelated within BS rocks. Samples from the GR horizon represent a unique composition with higher proportions of Thaumarchaeota and uneven distribution of Euryarchaeota and Bathyarchaeota affiliated to Methanomicrobia, SAGMCG-1, FHMa11 terrestrial group, AK59 and unclassified taxa. Acetoclastic methanogenic Methanomicrobia, autotrophic SAGMCG-1 and MCG of Thaumarcheaota could be identified as the signature groups within the organic carbon lean GR horizon. Sulfur-oxidizing Sulfolobaceae was relatively more abundant in sulfate-rich amygdaloidal basalt and migmatitic gneiss samples. Methane oxidizing ANME-3 populations were found to be ubiquitous, but their abundance varied greatly between the analyzed samples. Changes in diversity pattern among the BS and GR horizons highlighted the significance of local rock geochemistry, particularly the availability of organic carbon, Fe2O3 and other nutrients as well as physical constraints (temperature and pressure) in a niche-specific colonization of extremophilic archaeal communities. The study provided the first deep sequencing-based illustration of an intricate association between diverse extremophilic groups (acidophile-halophile-methanogenic), capable of sulfur/iron/methane metabolism and thus shed new light on their potential role in biogeochemical cycles and energy flow in deep biosphere hosted by hot, oligotrophic igneous crust.